A review: Organizational performance and its impact on project efficiency, business success, and future-readiness - Khairul Firdaus, Anuar; Nurhaizan, Mohd Zainudin; Muhammad Ashraf, Fauzi; Muhammad Hafis, Mohd Hussain (Karya Ilham Publishing, 2025)
In today's dynamic business environment, organizations must continuously strive to enhance their performance to achieve sustainable success. This review paper explores the various aspects of organizational performance and its impact on project efficiency, business success, and future readiness. This paper delves into the intricate connections between these elements, examining how organizational performance acts as a driving force behind achieving project milestones, fostering sustainable business growth, and positioning organizations for future adaptability and success. Organizational performance is a critical factor in the success and sustainability of construction organizations. Hence, construction organizational performance encompasses a construction company's ability to accomplish its strategic goals and objectives. Effective project management practices, coupled with a skilled and motivated workforce, are essential for delivering projects on time, within budget, and to the required quality standards. The qualitative methodology employed for this study includes content analysis techniques. Focusing on the Malaysian construction industry context, the paper examines how organizational performance affects these dimensions and discusses strategies for enhancing performance. Throughout the review paper, a wealth of real-world evidence is presented, including case studies, industry benchmarks, and academic research, to validate the relationships between organizational performance and its impact on project efficiency, business success, and future readiness.